(untitled) (Marketing Journal, 2025)
This article analyzed the country risk and economic stability of the Czech Republic based on the “Country Risk Assessment Model” (CRAM) developed by the Organisation for Economic Co -operation and Development (OECD). The study examined the Czech Republicʼs status as a high -income OECD member, its export oriented economy, and stable integration into the European Union, which collectively positioned it as a low -risk country. Both the quantitative and qualitative indicators of the CRAM framework were assessed, focusing on the nationʼs financial condition, geopolitical advantages, and external vulnerabilities.